Nanosized palm bunch ash (NPBA) stabilisation of lateritic soil for construction purposes - Chibuzor Onyelowe, Kennedy (International Journal of Geotechnical Engineering, 2017)
The stabilisation potential of Nanosized palm bunch ash (NPBA) was investigated. This investigation was aimed at assessing the effect of NPBA on the stabilisation of Umuntu Olokoro lateritic soil. The soil was studied under varying proportions of the NPBA mixed at 0% (control), 3, 6, 9, 12 and 15% by weight of the stabilised soil. The soil properties’ tests; soil classification or grading test, specific gravity, compaction test, consistency limits tests, unconfined compressive strength (UCS) test, California bearing ration (CBR) test and UV/VIS spectrophotometric characterisation were conducted. The UV–VIS test was conducted on the ash and the lateritic soil to determine their absorbance, wavelength and average particle size. The results of the preliminary tests showed that the soil was classified as A-2-7 soil on AASHTO classification with group index of “0” a Matlab program run on the sample also predicted that the soil is made of silty or clayey gravel and sand and that the general rating as a sub-grade material was “GOOD”. The average particle size of the ash by Debye Scherrer’s method was 11.358 nm and the maximum absorbance was 1.120 nm at the wavelength of 650 nm. The optimum moisture content OMC increased at 12 and 15% by weight of NPBA compared to the 0% NPBA proportion, which gave 13%. The Maximum Dry Density (MDD) decreased from 1.84 to 1.72 kN/m2 followed by a consistent increase in the value as higher percentages of admixtures were added. It was observed that the 6% NPBA gave the highest value of MDD of 1.93 g/cm3 followed by 9% NPBA of 1.84 g/cm3. The California Bearing Ratio (CBR) test results showed high and low values of CBR with 9% NPBA, which gave the highest (CBR) value of 30%. 12% addition of the admixture (Nanosized Palm Bunch Ash) by weight gave the highest unconfined compressive strength value of 399.46 kN/m2 at 28 days curing time. The least percentage NPBA (3%) gave the lowest UCS value of 192.9746 kN/m2. From the general results recorded, it is important to note that using lower percentages of NPBA as an admixture in treating lateritic soil will yield considerably, poor results. If NPBA should be used, it should be in higher percentages. However, 12% NPBA by weight of stabilised soil gave the best results and is preferred for use to stabilise lateritic soils for construction purposes.
Keywords: Evaluation; Nanosized palm bunch ash; Stabilisation; Engineering soil